Monitoring Agricultural Drought Using GIS and Remote Sensing Technologies in Upper Brantas Watershed - RIZATUS SHOFIYATI; K. HONDA; N.T.S WIJESEKERA; . WIDAGDO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2002)
Droughts disasters occured in some parts of Indonesian area periodically. To anticipate land and crops caused by drought needs historical data and information. Remote sensing provides the good capability to achieve spatial distributed, wide area coverage and multi-temporal. The study purposes to utilize remote sensing technology for agricultural drought monitoring and assessing in Upper Brantas Watershed. This study had used NOAA AVHRR were achieved from clearest NOAA AVHRR data selected every month from April 1997 to November 1998 and Landsat TM acquired May and June 1997. The method used in this research considers the relationship among rainfall and fluctuation of NDVI and BT. The study shows that an NDVI value of less than 0,28 was recognized as an appropriate threshold for the identification of drought affected area. NDVI and BT have an inverse relationship. The value can be used to delineate the spatially distributed for agricultural drought monitoring and assessment. Moreover, the map can be used for helping to anticipate the drought risk by changing the cropping pattern and other farming system in drought areas.